The Methodology of al-Maturidiâs Qurâanic Exegesis: Study of Taâwilat Ahl al-Sunnah - Rofiq, Ahmad Choirul (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2009)
According to Islamic theology, al-Maturidi is one of the three prominent Muslim theologians of Ahl al-Sunnah wa al-Jamaah who are called aqtab madhhab Ahl al-Sunnah waâl-Jamaâah (the leaders of Sunnite school of thought). In addition to his reputation as a theologian, al-Maturidi actually was competent in various Islamic sciences. In Quranic exegesis, he has Taâwilat Ahl al-Sunnah or Taâwilat al-Qurâan. Unfortunately, this fact isnt known well by Islamic researchers. This article is going to elucidate the features of his work that encompass at least seven characteristics. Al-Maturidi prefers to combine the naqli (traditional) and âaqli (rational) sources. Consequently, it can be identified as tafsir biâl-izdiwaj or the exegesis that amalgamates tafsir biâl-maâthur (traditional exegesis) with tafsir biâl-raây (rational exegesis). He is not an interpreter who uses excessive grammatical analysis to interpret the Quranic verses. He sometimes presents many styles of qiraâah (recitation of the Quran) without thorough explanation. He almost never uses Israâiliyyat (the Judeo-Christian traditions and tales) to interpret the Quranic verses. He favors tawassut (nonaligned and independent standpoint) when he deals with different viewpoints among theologians. He tends to follow the Hanafite school of thought in discussing the jurisprudential Quranic verses. He applies asbab al-nuzul (the causes of revelation) loosely.